Post-traumatic existentiells in a literary text: the example of one short story by J. D. Salinger. - Паранюк, Дан; Тичініна, Альона (Дрогобицький державний педагогічний університет імені Івана Франка, 2023)
In terms of the topical issues of poetics, the article under studies outlines the specifics of post-traumatic existentiells of war in a literary text. A convincing example is the collection of short stories by the classic American prose writer Jerome David Salinger (1919–2010) “Nine Stories” (1953). In the methodological context of existential and literary anthropology, the author’s biographical traumatic experience is used to actualize the topic of post-traumatic existentiells of war. The article emphasizes the connection between literature and war through the prism of existentiells of the writer’s experience, as well as highlights the impact of J. Salinger’s war experience on his creative method. In addition, particular accent has been laid on the so-called symptoms of (post) traumatic writing typical for the authors of the ”Lost Generation” (depiction of traumatized characters who constitute the core of the personosphere, mostly centered on children; the presence of a plot containing several narrative plans of the story (autology, metaphor, symbol, myth); retrospective narratives of recollection, memorization of past traumatic experiences, fragmentary memories; deviation (ignoring) from the canons of genre and style; dialogicity; internal and external conflict; intertextuality and intermediality; playing with the reader). What is more, the article draws attention to the phenomenon of trauma in the field of literary anthropology, as well as defines the concept of post-traumatic existentiells and analyzes the post-traumatic existentiells of war in the collection “Nine Stories” (fear, loneliness, alienation, compassion; disappointment, love, and squalor). The short story ”For Esmé – with Love and Squalor” (1950) has been interpreted in this very respect. The leading existentiells of the short story (stated in its title) affect the main formal and substantive aspects of the work: theme, idea, genre, narrative, personosphere, conflict. Besides, the author’s designed mental state of the protagonist reflects the history of post-traumatic stress disorder. In conclusion, the article states that a literary text is able to accumulate the author’s post-traumatic war experience and activate its consonance with the current emotional state of the reader, who in such conditions is increasingly subject to empathy and catharsis.
Keywords: Poetics, prose, genre, existentiell, personosphere, conflict, symbol, mental state